Soil solarization in relation to potato production: A review - SINGH, RAJESH K; BUCKSETH, TANUJA; SHARMA, ASHWANI K; MOUDGIL, VAISHALI; CHAKRABARTI, S K; SINGH, A K (The Indian Journal of Agricultural Sciences, 2018)
Soil solarization is a non-chemical and non-hazardous method known to possess numerous beneficial effects in crop production . It is mainly useful for commercial application in areas with very high air temperatures during the summer; where much of the crop area is kept fallow - due to excessive heat. A review of the available information on soil solarization reveals the numerous advantages of the technique in relation to crop production. Solarization of soil has been reported to manage weeds, control nematodes, soil borne diseases and insects. Besides these, it increases thermo-tolerant micro-fauna in the soil, most of which are beneficial - the bioagents, nutrient solubilizers and nitrifiers, and thus results in higher availability of essential plant nutrients and improvement in soil tilth. The effectiveness of soil solarization as soil-borne pests control method is well demonstrated. In potato, soil solarization is known to increase the potato yield coupled with better quality of tubers through the reduction of several soil borne diseases and weeds.